2008
DOI: 10.1073/pnas.0709513105
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the promoter–σ region 1.2 interaction

Abstract: We recently proposed that a nontemplate strand base in the discriminator region of bacterial promoters, the region between the ؊10 element and the transcription start site, makes sequence-specific contacts to region 1.2 of the subunit of Escherichia coli RNA polymerase (RNAP). Because rRNA promoters contain sequences within the discriminator region that are suboptimal for interaction with 1.2, these promoters have the kinetic properties required for regulation by the RNAP-binding factors DksA and ppGpp. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 30 publications
7
95
1
Order By: Relevance
“…These data support the model that the nontemplate strand G rather than the template strand C accounts for the TSS shift with the C-7G promoter and indicate that the identity of the -7 position on the nontemplate strand, not the G+C content of the discriminator, is responsible for these effects. We showed previously that the nontemplate strand G of the C-7G promoter interacts with σ 1.2 (16), and subsequent genetic studies (21) and structural studies (22) showed that σ residues M102 and R103 contribute to this interaction. We therefore compared the TSSs produced by the wild-type RNAP and σ M102A/R103A mutant RNAP and by the C-7G and rrnB P1 Dis promoters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data support the model that the nontemplate strand G rather than the template strand C accounts for the TSS shift with the C-7G promoter and indicate that the identity of the -7 position on the nontemplate strand, not the G+C content of the discriminator, is responsible for these effects. We showed previously that the nontemplate strand G of the C-7G promoter interacts with σ 1.2 (16), and subsequent genetic studies (21) and structural studies (22) showed that σ residues M102 and R103 contribute to this interaction. We therefore compared the TSSs produced by the wild-type RNAP and σ M102A/R103A mutant RNAP and by the C-7G and rrnB P1 Dis promoters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The discriminator region between the −10 hexamer and the transcription start site (TSS; +1) has recently emerged as an important modulator of the open complex properties (11)(12)(13)(14)(15)(16)(17)(18). In a stable open complex formed by Thermus thermophilus RNAP, the −6 and −5 bases of the discriminator NT strand (NT DISC ) make crucial contacts with σ1.2, and βArg371 (E. coli numbering) interacts with the adjacent −4 and −3 bases (14).…”
Section: Resultsmentioning
confidence: 99%
“…Substitutions of the discriminator bases and the σ and β residues that interact with the NT strand lead to decreases in open complex stability (11,14,16). To test whether the loss of the GL-NT DISC contacts observed in the RPo structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1B). A comparable mutation in the ribosomal promoter rrnB P1 has been shown to increase RPo half-life via interaction with 70 region 1.2 residue M102 and, in addition, the absence of region 1.1 increases the detection of this contact (22,33). P min11 is also inhibited by region 1.1 (Fig.…”
Section: Effectmentioning
confidence: 94%
“…Finally, the DNA around the ϩ1 site begins to melt, and 70 region 2.3 contacts single-stranded (ss)DNA bases at positions Ϫ10 through Ϫ7 on the nontemplate strand. For some promoters, contract(s) between residues in 70 region 1.2 and ss bases at Ϫ5 and Ϫ6 occurs also (22,33). The protein/ssDNA interactions stabilize the polymerase/promoter complex, allowing the template strand to descend into the active site of core and the dsDNA downstream to fully enter the downstream channel.…”
mentioning
confidence: 99%